Let this Hell be Our Heaven: Richard Matheson's Spirituality and Its Hollywood Distortions - Moreman, Christopher M. (Journal of religion and popular culture, 2012)
Richard Matheson's 1954 novel, I Am Legend, has inspired three official, and other unofficial, film adaptations. Hollywood has, however, consistently altered key elements, severely distorting the novel's themes. Where I Am Legend is predictive of the anti-authoritarianism of the counterculture, Matheson's later work aligns closely with spiritual elements of the so-called New Age. This article will show how Hollywood adaptations increasingly promote distinctly Christian symbolism in opposition to Matheson's own spirituality, nascent in I Am Legend.